Violência de gênero contra as mulheres: o trabalho social no CRAS na perspectiva da proteção social básica da Política de Assistência Social no município de São Paulo - Felix, Karina (2022)
The object of this dissertation is the way in which gender violence against women has been perceived and addressed in the basic social protection of the Social Assistance policy in the city of São Paulo. Your objective focused on questioning the limits and possibilities to develop the social work in CRAS with women victims of violence, in its multiplicity of manifestations, in the welcoming activity and in the socio-educational work offered, although the competence for dealing with these situations is attributed to special social protection and, therefore, to CREAS. Female service users form the largest public served by the social work of CRAS, and therefore, issues related to the various gender violence against they are brought up daily, either explicitly, when they verbalize this issue in their request for assistance; or implicit, when their narrative reveals evidence that demands attention. The analysis was structured from two articulated thematic axes: the first affirms the understanding that violence against women is expressed under concrete conditions specific to the capitalist mode of production, colonialist, patriarchal and slaveholder, which affect the materiality and subjectivity, imprinting meanings on their forms of conscience, values, conduct and on the morality constructed. The second thematic axis refers to the current stage of structuring the Social Assistance in the city of São Paulo, its unfinished historical construction and the working conditions for its operationalization. The reflection on the concept of basic social protection that guides the work of reception in the CRAS was deepened, considering forms of organization, working conditions and the limits and possibilities of articulation between CRAS and CREAS. The qualitative methodology was chosen to carry out the study, which was composed of bibliographic, documentary and empirical research, all related to thematic axes. Six interviews were carried out, remotely, with professional workers from CRAS and CREAS and members of CRESSSP and COMAS-SP, based on a semi-structured script composed of ten questions. The research highlighted the current fragility of the Social Assistance policy in defining consolidated procedures and flows for articulated social work, so that the answers to social needs do not remain fragmented by levels of social protection. Although the fundamental role of CRAS is recognized in the qualified reception of situations of violence against women and their preventive work in the face of this social issue, social work has been permeated by precarious working conditions that, together with the plurality of conceptions of professionals, the absence of continued professional training and spaces for collective construction between the teams that make up the social assistance services, have meant an obstacle in the realization of social work in consonance with the parameters of the SUAS and in the decoding of its regulations in actions that dialogue with the social reality of its users. Individualized actions remain in the different territories of the city, whose reception process and socio-educational work with women subjected to gender violence remains under the scrutiny of each professional, in the use of their relative autonomy